KEABSAHAN PERKAWINAN MELALUI MEDIA ONLINE MENURUT HUKUM HINDU DAN HUKUM POSITIF - Nida Luqyana (2022)
In this era we are benefited by the advancement of technology where everything is done by online such as buying food, clothes etc. no exception for the process of marriage with the availability of facilities for communicating in the form of a video we can meet with our relatives even though we are seperated by a great distance. As performed by the bride and groom Indonesian citizens and foreign nationals from Australia who hold a marriage through online media because of the unobstructed distance and the conditions of the pandemic-covid19. As well as a pair of citizens of the state of Indonesia who hold marriage online between Japan and Indonesia. but basically in the Law No. 1 Year 1974 about Marriage. marriage through online media has not had a rule that specialized in Indonesian positive law. Knowing the problems that occur, the researchers use a method that is qualitative based on the mapping news online selected based on the theme of the news that meets the criteria of the focus of research as well as with normative juridical approach that is where the analysis is based on the laws and regulations applicable coupled with interviews to related parties. The conclusion of marriage through online media based on the law of the hindus, and positive law is valid if it has been eligible.